Optimization of farmer groups and educational tourism of Bamboe Wanadesa - Arif Wicaksono Septyanto; Muhammad Ikhsan Alif (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The implementation of community service activities exemplifies the essence of the Tri Dharma of Higher Education. This initiative is based at Wisata Bamboe Wanadesa on Jl. Giri Rejo KM 15, Karang Joang Village, North Balikpapan District, Balikpapan City, leveraging its bamboo forest resources for tourism. However, a deficiency in human resources is apparent in managing social media, graphic design, branding, and promotion for this attraction. The absence of knowledge among residents and tourists about the bamboo varieties also persists. To address these gaps, we conducted community service through diverse approaches. Workshops were conducted to train content creators using CapCut and Canva applications, enhancing social media visibility. Google Site was employed to bolster tourism branding, serving as an information hub. Furthermore, information boards strategically placed within Bamboe Wanadesa Tourism, interconnected with Google Site, were introduced. The outcomes encompass collaborative Instagram content, the Bamboe Wanadesa website, and informative plant labels, significantly contributing to improved engagement and knowledge dissemination.